Estimation of a midfoot joint center in typically developed adults using functional calibration methods - Salami, Firooz; Götze, Marco; Campos, Sarah; Leboucher, Julien; Hagmann, Sébastien; Wolf, Sebastian Immanuel (Gait & posture, 2022)
Background - There are detailed findings on hip and knee joint parameters determined via functional calibration methods for use in instrumented 3D-gait analysis but these methods have not yet been addressed to the foot. - Research question - Are functional calibration methods feasible for determining foot joint parameters and may they help for clinical interpretation of foot deformities? - Methods - Rigid segments were formed by markers on forefoot and hindfoot via a least square method. The position of the midfoot joint articulating both foot segments was then determined via a functional calibration motion. This two-stage procedure was applied on a cohort of 17 typically developed adults and one subject with severe planovalgus foot deformity for determining the location of the midfoot joint and kinematics of hindfoot and forefoot. - Results - The position of the midfoot joint center could be estimated in the typically developed cohort and also in the demonstration case with planovalgus foot deformity. Depending on the choice of marker set for hindfoot and forefoot, the position of the joint center varied in the anatomic midfoot region with most robust results when addressing the marker on the navicular to the hindfoot. - Conclusion - The presented method for joint center determination within the foot and the characteristic results of the foot joint angles appear promising for typically developed feet. However, further validation of the method is needed for application in clinical context.
Online veröffentlicht: 17. August 2022
Gesehen am 19.10.2022